Application of glass and fan shells to a clay soil to increase its mechanical properties - Jara, Heiner Lopez (2021)
Improving the mechanical properties of a clayey soil is one of the best options to avoid future structural failures in buildings and is cheaper than replacing all the material. Therefore, this article proposes the use of recycled glass and fan shells as reinforcement materials. This article presents an experimental study to evaluate the mechanical properties of a pure and mixed soil. The clay soil was mixed with 7% of glass (PV) and with 3%, 6%, 10%, 12% and 15% of Fan Shells (PCA) duly crushed and passed through sieve #100. Tests of sieve granulometry, sedimentation granulometry, Atterberg limits, modified proctor and drained consolidated direct cut were performed. This allowed comparing all the data obtained and defining the optimal percentage of the mixture in which the clay improves its mechanical properties. According to the tests carried out, the proportion that has 7% glass and 6% Fan Shells has better results because there is an improvement in its dry density from 1,784 g / cm3 to 1,847 g / cm3, its moisture content increases from 9.4% to 12.1%. In addition, its friction angle improves from 28.9 °to 32 °and cohesion from 0.05 kg / cm2 to 0.1 kg / cm2. These results verify that the properties of the clay soil are improved.